Be Real, Do Not Be Fake: A Pilot Study On Universiti Sains Islam Malaysia Students' Fake News Literacy - Afiqah Mior Kamarulbaid; Muhammad Raqib Mohd Sofian; Nurul Nadirah Abu Hasan; Nurul Fathihin Mohd Noor Shah; Norsimaa Mustaffa; Mohamad Hafizuddin Mohamed Najid; Mohd Faridh Hafez Mhd Omar (Fakultas Dakwah UIN Saizu Purwokerto - Indonesia, 2024)
Non-Indexed Publication